PENGARUH PEMBERIAN KOMPOS DAN NPK MUTIARA TERHADAP PERTUMBUHAN DAN HASIL BAWANG DAUN (Allium fistulosum L.) - Mohamad Fadli; Syahrani Syahrani; Gilang Wisnu Irawadi (Jurnal Magrobis, 2021)
This study aims to determine the effect of compos and NPK fertilizer on   growth and yield of onion leaf (Allium fistulosum L.). This research started from Desember 2020 to February 2021, located in Sumber Sari Village, Loa Kulu District, Kutai Kartanegara Regency, East Kalimantan Province. The research was arranged in a Randomized Complete Block Design (RCBD) with a single factorial analysis with three replications. The first factor of treatment was solid administration (S) consisting of 7 levels of s0 (without fertilizer), s1 = 5 t ha-1 (1.8 kg plot-1), s2 = 10 t ha-1 (3.6 kg plots-1), s3 = 15 t ha-1 (5.4 kg plot-1), s4 = 20 t ha-1 (7.2 kg plot-1), s5 = 25 t ha-1 (9 kg plot-1),  and s6 = 30 t ha-1 (10.8 kg plot-1). The results showed that solid treatment had a significant effect on five parameters, plant age at flowering, flower diameter, harvest age, flower weight on plants and crop yield per hectare (t ha-1). The highest yield per hectare was in s6 treatment with an average of 16.29 t ha-1.